Method and Algorithm for Determining Weaknesses in a Distributed Database - Sadikov Sh.M. (Global Scientific Publishing, 2023)
The article analyzes the SQL injection attack and its types in the distributed database, the vulnerability search algorithm, the vulnerability detection algorithm by query analysis in the MySQL (SQL) database, linear search algorithm, binary search algorithm, interpolation search algorithms have been developed
Keywords: SQL injection; classic and blind SQL-injection; offline injection